Aflatoxins: A Global Concern for Food Safety, Human Health and Their Management - Kumar, Pradeep; Mahato, Dipendra K.; Kamle, Madhu; Mohanta, Tapan K.; Kang, Sang G. (Frontiers in Microbiology, 2017)
The aflatoxin producing fungi, Aspergillus spp., are widely spread in nature and have severely contaminated food supplies of humans and animals, resulting in health hazards and even death. Therefore, there is great demand for aflatoxins research to develop suitable methods for their quantification, precise detection and control to ensure the safety of consumers’ health. Here, the chemistry and biosynthesis of the mycotoxins is discussed their occurrence and the health hazards to humans and livestock. This review focuses on resources, production, detection and control measures of aflatoxins to ensure food and feed safety. The results presented herein will facilitate health-conscious consumers and for experts, while providing knowledge on new and innovative approaches to ensure food safety and meet the future demands of the increasing population by decreasing the incidence of outbreaks by aflatoxins.